Grit in waterfowl at the Ouse Washes, England - Thomas, G J; Owen, Myrfyn; Richards, Penny (Wildfowl, 1977)
Grit was examined from the gizzards of 596 wintering waterbirds shot at the Ouse Washes, England. All contained some grit but the range of weight was high for most species. The amount of grit is to some extent related to gizzard size, ranging from an average of 0.9 g in Teal Anas crecca to 4.5 g in Wigeon and 69.8 g in Mute Swans Cygnus olor. Only in Tufted Duck did the size distribution of grit resemble that from local gravel pits. Most of the grit was silica (quartz). The Ouse Washes soil is predominantly peat and may be deficient in grit. Wigeon here contain about two-thirds the amount of those wintering at Bridgwater Bay, Somerset. It is suggested that deposition at the Ouse Washes of grit from unshot gravel pits should be increased.